Correlation Between Nutritional Status Of Children Aged 12 – 36 Months And Mother’s Working Status In Taman, Sidoarjo - Nur Annisa Nugraheningtyasari; Ninik Asmaningsih Soemayarso; Dwi Susanti (Faculty of Medicine, Universitas Airlangga, Surabaya, Indonesia, 2018)
Introduction: The correlation between child’s nutritional status and mother’s working status in Indonesia is still unclear. Some research report a high prevalence of low-nourished children whose mother is working, while others report a non significant correlation between child’s nutritional status and mother’s working status.Methods: This study was case-control study, sample of low-nourished children (treatment group) & well-nourished children (control) are taken from 21 Posyandu in Taman, Sidoarjo in 2015. All data were analyzed using Chi Square test.Results: There are 72 samples which are suitable with the inclusion criteria, consisted of 36 low-nourished children and 36 well-nourished children. From 72 samples, 28 children have a working mother and 44 children have a non working mother. There were no correlation between Mother’s working status (p=0,486), Number of children in the family (p=0,468), History of chronic disease (p=0,054) with child’s nutritional status. Level of family income, Mother’s education level, History of exclusive breastfeeding, Energy consumption level, Protein consumption level were correlated with child’s nutritional status with value (p=0,000), (p=0,002), (p=0,002), (p=0,000), (p=0,001) respectively.Conclusion: Mother’s working status is proved that is not correlated with child’s nutritional status. But, level of family income, mother’s education level, energy & protein consumption level, and history of exclusive breastfeeding are significantly correlated with child’s nutritional status.